Autonomy-supportive treatment for acquired apraxia of speech: feasibility and therapeutic effect. Issue 4 (3rd April 2021) - Haley, Katarina L.; Cunningham, Kevin T.; Kim, Ian; Shafer, Jennifer S.
ABSTRACT: Background : Most treatments for acquired apraxia of speech (AOS) rely on clinician-controlled practice conditions and repeated exposure to unimpaired speaker models. Recent motor learning research indicates that autonomy-support, expectation of competence, and external attentional focus may be more beneficial for motivation and skill learning. Aims : We evaluated the feasibility and basic therapeutic effect for the initial phase of a new speech production treatment program, ActionSC, that uses self-modeling and clinician coaching to help learners with AOS build their own practice program. Methods and Procedures : The single participant was a woman with moderate AOS and nonfluent aphasia. She met with project staff twice per week to review practice strategies, develop and adjust self-modeled video cues, work on her speech, and monitor progress. The program was structured around a custom app installed on a tablet computer. Most practice was directed by the participant based on options provided by the treating clinician. We used a multiple baseline across behavior design to evaluate the relationship between this treatment and oral reading probe performance for 30 conversational phrases the participant wanted to learn to say. Outcomes and Results : Experimental control was demonstrated, with target phrases remaining at baseline levels, then improving at the time treatment was introduced sequentially across three conversation topics. Effect sizes were moderate to large after 9–12 therapy sessions plus independent home practice. The participant assumed an active role in evaluating her own performance, administering and adjusting cues, and organizing her home practice. Conclusions : An autonomy-supportive and confidence-building format for speech practice can be feasible and effective for people with AOS. Fixed cueing hierarchies, augmented feedback, and attentional focus on speech movements may be less important in AOS treatment than previously thought. In addition to replicating our preliminary results with other participants and circumstances, there is a need to extend treatment development to later learning phases in order to promote positive change in real-life settings.